Intermolecular Electronic Coupling of Organic Units for Efficient Persistent Room‐Temperature Phosphorescence. Issue 6 (6th January 2016) - Yang, Zhiyong; Mao, Zhu; Zhang, Xuepeng; Ou, Depei; Mu, Yingxiao; Zhang, Yi; Zhao, Cunyuan; Liu, Siwei; Chi, Zhenguo; Xu, Jiarui; Wu, Yuan‐Chun; Lu, Po‐Yen; et al.
Abstract: Although persistent room‐temperature phosphorescence (RTP) emission has been observed for a few pure crystalline organic molecules, there is no consistent mechanism and no universal design strategy for organic persistent RTP (pRTP) materials. A new mechanism for pRTP is presented, based on combining the advantages of different excited‐state configurations in coupled intermolecular units, which may be applicable to a wide range of organic molecules. By following this mechanism, we have developed a successful design strategy to obtain bright pRTP by utilizing a heavy halogen atom to further increase the intersystem crossing rate of the coupled units. RTP with a remarkably long lifetime of 0.28 s and a very high quantum efficiency of 5 % was thus obtained under ambient conditions. This strategy represents an important step in the understanding of organic pRTP emission. Abstract : Persistence pays off : Bright persistent room‐temperature phosphorescence from pure organic molecules was achieved by intermolecular electronic coupling of selected units in crystals. The combined advantages of their different excited‐state configurations (i.e., the nπ* state with a high intersystem crossing rate and the ππ* state with a low radiative rate) results in a hybrid intersystem‐crossing process that leads to efficient persistent room‐temperature phosphorescence.